2012
DOI: 10.1002/ange.201105922
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Measurement of Surface Electron Transfer on Reduced Molybdenum Oxides (MoOx) and Catalytic Activities of Au/MoOx

Abstract: Der Nachweis von Elektronen, die sich in Oberflächendefektzentren befinden, wird vorgestellt. Mit Tetracyanoethylen als Einelektronenakzeptor wurde die Reduktion von vollständig oxidiertem MoO3 charakterisiert. Durch Elektronentransfer gelangt negative Ladung zu auf der Oberfläche befindlichen Goldnanopartikeln, was die hohe katalytische Aktivität bei der aeroben Oxidation von Alkoholen erklärt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It is reported that the presence of negative charge on the Au core would enhance the catalytic activity of Au for aerobic oxidations. [64][65][66] Recent theoretical calculations also confirm that this interaction can increase the reaction activity. [67] Therefore, we conclude that these strong interactions transfer the charge to the Au cluster and lead to the high performance of the reaction (Scheme 1 B), besides protecting the gold nanoclusters against sintering.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is reported that the presence of negative charge on the Au core would enhance the catalytic activity of Au for aerobic oxidations. [64][65][66] Recent theoretical calculations also confirm that this interaction can increase the reaction activity. [67] Therefore, we conclude that these strong interactions transfer the charge to the Au cluster and lead to the high performance of the reaction (Scheme 1 B), besides protecting the gold nanoclusters against sintering.…”
Section: Resultsmentioning
confidence: 83%
“…This charge transfer makes the gold cluster more electronegative, which facilitate the HMF oxidation. It is reported that the presence of negative charge on the Au core would enhance the catalytic activity of Au for aerobic oxidations 6466. Recent theoretical calculations also confirm that this interaction can increase the reaction activity 67.…”
Section: Resultsmentioning
confidence: 93%
“…Wang et al have used a supported Au/MoO x heterogeneous catalyst for the aerobic oxidation of alcohols to aldehydes in high yields (eq 26). 28 In their study, the authors confirmed that electron transfer from the partially reduced MoO x support to the Au NPs would result in negatively charged Au cores, yielding highly active catalysts for the selective aerobic oxidation of alcohols. In a related earlier study, Au clusters smaller than 1.5 nm stabilized by poly(Nvinyl-2-pyrrolidinone) (PVP) were used as active catalysts for the aerobic oxidation of alcohol to aldehyde (eq 27).…”
Section: Semiconductor-metal Nanocompositesmentioning
confidence: 86%
“…Wang et al have used a supported Au/MoO x heterogeneous catalyst for the aerobic oxidation of alcohols to aldehydes in high yields (eq ) . In their study, the authors confirmed that electron transfer from the partially reduced MoO x support to the Au NPs would result in negatively charged Au cores, yielding highly active catalysts for the selective aerobic oxidation of alcohols.…”
Section: Semiconductor-metal Nanocompositesmentioning
confidence: 91%
“…In this way, the conversion of transesterification (X b ) was obtained from GC injection of the extracted product, and a linear relationship was provided between À ln(1-X b ) and the reaction time in agreement with the literature. [35,36] Also, the kinetics was obtained for normal MeOH (Figure 2a).…”
Section: Catalyst Activitymentioning
confidence: 90%